Pycnogonids (Arthropoda: Pycnogonida) of Portofino, Ligurian Sea (North-Western Mediterranean Sea). Issue 1 (1st January 2019) - Galli, L.; Colasanto, E.; Betti, F.; Capurro, M.
Abstract: Pycnogonida collected monthly from September 2017 to August 2018 in the Portofino Marine Protected Area at 0–5 m depth were studied. A total of 499 specimens were collected, 457 of which were identified to species level. These were classified as belonging to 10 species: Achelia echinata*, Ascorhynchus castelli, Neotrygaeus communis*, Tanystylum conirostre*, Anoplodactylus angulatus, A. petiolatus, A. pygmaeus*, A. virescens, Callipallene phantoma and C. tiberi* . For five dominant species (those marked with an asterisk) the annual phenology was outlined. Four hundred and seventeen additional specimens, collected from the same area and depth range mainly during the 1970s and 1980s were identified to species level for completeness of information, leading to the addition of Pycnogonum pusillum and Endeis spinosa .